1979
DOI: 10.1104/pp.64.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Anaerobic Metabolites Accumulating in Winter Wheat Seedlings during Ice Encasement

Abstract: Ice encasement damages cold-hardened winter wheat without major disruption of cellular organelles. CO2 accumulates during total ice encasement to higher levels in Kharkov than in less hardy Fredrick wheat. Partial ice encasement and exposure to a nitrogen atmosphere at -1 C allows greater CO2 accumulation but neither treatment is as damaging as total ice encasement. Lactic acid accumulates to low levels only during the 1st day of Damage to winter cereal plants during ice encasement at mild subfreezing temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 14 publications
0
36
0
1
Order By: Relevance
“…Metabolites of anaerobic respiration, such as ethanol, CO2, and lactic acid accumulate in tissues of winter cereals during ice encasement (1,4,18,21) and flooding at low temperature (7,19). 02 consumption of tissue segments and mitochondria from ice-encased seedlings declines more slowly than the decline in seedling viability (3,18 'To whom reprint requests should be forwarded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolites of anaerobic respiration, such as ethanol, CO2, and lactic acid accumulate in tissues of winter cereals during ice encasement (1,4,18,21) and flooding at low temperature (7,19). 02 consumption of tissue segments and mitochondria from ice-encased seedlings declines more slowly than the decline in seedling viability (3,18 'To whom reprint requests should be forwarded.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane permeability to amino acids and salts increases markedly during ice encasement or exposure to CO2 and ethanol at -1°C (4).…”
mentioning
confidence: 99%
“…The initial decrease can be attributed to the effects of anaerobiosis as a decrease in FR did not occur in leaves treated similarly but under aerobic conditions. Andrews and Pomeroy (2) showed that the anaerobic metabolite lactic acid increased during the 1st d of ice encasement and then remained constant.…”
mentioning
confidence: 99%
“…Two cultivars of wheat were compared, Kharkov winter wheat which has a high tolerance to ice encasement (2) and Gatcher spring wheat. During the first day under N2 at0WC, the FR of the leaves of both cultivars decreased by more than 50%o and thereafter decreased much more slowly.…”
mentioning
confidence: 99%
“…Ethanol is produced by flooded seedlings (1,18,19), ice encased leaves (2), root nodules (20), and tissues exposed to S02 and 03 (10). The endosperm of germinating castor bean endosperm is an appropriate model to study anaerobic stress and alcohol metabolism.…”
mentioning
confidence: 99%